2018
DOI: 10.1200/jco.2018.36.34_suppl.57
|View full text |Cite
|
Sign up to set email alerts
|

State-level differences in personality and geographic disparities in access to palliative care: Findings on openness.

Abstract: 57 Background: There are geographic disparities in access to palliative care that cause unnecessary suffering near the end of life in low-access U.S. states. The psychological mechanisms explaining state-by-state variation in access to palliative care are poorly understood. Our objective was to examine whether state-level differences in personality explain state-by-state variation in palliative care access. Methods: We combined four datasets with state-level data for the 50 U.S. states and the national capito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…31,93 There are also geographic disparities in access to palliative care in United States, suggesting that access to such care is worse among more racially diverse, poorer, and more politically conservative states. 52 Overwhelming evidence, based on large national data sets, consistently and unequivocally points to major disparities in palliative care in the United States. 13,39,40,55,64 One retrospective cohort study of over 5 million hospitalizations of dialysis patients revealed that non-Hispanic Black and Hispanic patients were less likely than non-Hispanic White patients to receive palliative care services in the hospital.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…31,93 There are also geographic disparities in access to palliative care in United States, suggesting that access to such care is worse among more racially diverse, poorer, and more politically conservative states. 52 Overwhelming evidence, based on large national data sets, consistently and unequivocally points to major disparities in palliative care in the United States. 13,39,40,55,64 One retrospective cohort study of over 5 million hospitalizations of dialysis patients revealed that non-Hispanic Black and Hispanic patients were less likely than non-Hispanic White patients to receive palliative care services in the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…After searching almost fourthly-thousand citations, 284 articles were included in our study, of which 147 were manuscripts that directly addressed end-of-life and hospice care, palliative care, as well as advance care planning and directives that include non-Hispanic Blacks. 4 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…25-46 The racial disadvantage has also been documented throughout the literature for adults who receive specialized services, such as palliative care for people with serious illness or hospice services for people approaching the end of life. 17,47-72 The racial disparities persist into end-of-life care, particularly regarding communication and family needs. 73…”
Section: Introductionmentioning
confidence: 99%